Phytostilbenoid production in white mulberry (Morus alba L.) cell culture using bioreactors and simple deglycosylation by endogenous enzymatic hydrolysis - Jukrapun Komaikul (2020)
© 2018, The Society for In Vitro Biology. Phytostilbenes are responsible for several biological activities of mulberry (Morus sp.), which has been widely used as a raw material in health products. This study aimed to investigate the capability of Morus alba L. cell in bioreactors to produce the major bioactive stilbenes. The cell obtained from air-driven bioreactors such as round bottom, flat bottom, and air-lift vessel shape bioreactors was collected and analyzed for the levels of mulberroside A and oxyresveratrol. The results showed that the cell culture in round bottom and air-lift vessel bioreactors had higher growth rate, as compared with the cell culture in shake flasks (1.38- and 1.41-fold, respectively). The optimized culture condition to produce mulberroside A was obtained from round bottom bioreactor culture (55.56 ± 11.41 μmol/L). Additionally, endogenous stilbenoid hydrolysis of cell from the bioreactor culture was examined. Under optimized hydrolytic conditions, mulberroside A in the cell was readily deglycosylated to give oxyresveratrol within 1 h. These results indicated that the glycoside mulberroside A in the cell is sensitive to the endogenous enzymatic hydrolysis. Interaction of the stilbenoid components with the endogenous hydrolytic enzyme triggered by cell disruption in M. alba samples was suggested to be the major cause of the alteration of the stilbenoid levels. These findings have provided a new approach to producing glycosidic compounds and corresponding aglycones in cell culture.